Open data for the crowd: an account of citizen science at ETH Library - Wiederkehr, Stefan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
This paper gives an account of ETH Library’s combined strategy of implementing an open data policy and using crowdsourcing to improve metadata. Both activities go hand in hand and promote each other. ETH Library’s Image Archive was the first unit to provide content for free download in high resolution. This paved the way for a very successful crowdsourcing campaign during which citizen scientists located places, dated photographs, and identified people and artefacts. This positive experience led to further crowdsourcing activities in other ETH Library units. Important conditions for success apart from the open data policy were conscious community management by social media channels and promoting competition within a gamification approach.